On a form of Lyapunov exponents (I: Establishment of the form) - Dinh, Nguyen Van (Vietnam Journal of Mechanics, 2004)
Another form of Lyapunov exponents associated with certain motion that given by (1.2) is proposed. It is expressed through the variation of the disturbance direction (not through that of the disturbance norm).